Liquid smoking as a method for addressing polycyclic aromatic hydrocarbons (PAH) in traditional masmin - Nithin, C. T.; Joshy, C. G.; Chatterjee, Niladri Sekhar; Panda, Satyen Kumar; Yathavamoorthi, R.; Ananthanarayanan, T. R.; Mathew, Suseela; Bindu, J.; Srinivasa Gopal, T. K. (Indian Journal of Fisheries, 2018)
Masmin is a traditional smoked and dried product from Lakshadweep Islands, Union territory of India. Intensive smoking practiced during production of masmin leads to chances of accumulation of carcinogenic compounds like polycyclic aromatic hydrocarbons (PAH) in the product. The aim of this study was to develop liquid smoked masmin which has matching flavour with traditional masmin and lower content of PAH. Response surface methodology was used for standardisation of the products. It was observed that spraying cooked tuna loins with a commercial liquid smoke â€œSMOKEZ ENVIRO 24PBâ€ (diluted in 1:6 proportion with distilled water and added with 3.5% (w/v) salt) for 150 min at a flow rate of 1l h-1 in a multi-functional smoke kiln at a chamber temperature of 60Â°C was effective in giving desirable flavour for the product. Analysis of PAH content in traditional masmin showed values exceeding the national and international standards. However, liquid smoked masmin had a PAH content which is well within the recommended level. Shelf life evaluation of the products revealed that they have shelf life of more than 12 months at ambient temperature.